What is the largest integer n for which n 2 + 2 4 n + 1 6 is a perfect square?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If a nonnegative n exists, then clearly it is larger than any negative value of n . We assume n is nonnegative.
Note that ( n + 4 ) 2 ≤ n 2 + 2 4 n + 1 6 < ( n + 1 2 ) 2 .
Checking all possible perfect squares between the bound, we can easily get the largest possible integer n .
Actually,we can further reduce the work by checking ( n + a ) 2 for which a is even.
I can't understand how you can determine all the perfect squares between the bounds. I assume the bounds are ( n + 4 ) 2 and ( n + 1 2 ) 2 . The fact that these bounds depends on n leaves me a bit quizzed. If you can help me I will greatly appreciate.
Because the expression in question is a perfect square,then considering the bounds, we have either n 2 + 2 4 n + 1 6 = ( n + 4 ) 2 , ( n + 5 ) 2 , ( n + 6 ) 2 , … , or ( n + 1 1 ) 2 . Solving these diophantine equations shows that no such value exist.
For n = 0 we clearly have a perfect square ( 1 6 ). So we can restrict our search among the positive integers.
Since n is positive the expression n 2 + 2 4 n + 1 6 is greater than n 2 so if it is perfect square, then it must be written as ( n + p ) 2 for some positive integer p .
So
n 2 + 2 4 n + 1 6 = ( n + p ) 2
leads to
2 n ( p − 1 2 ) = 1 6 − p 2
Now you can easily note 3 interesting facts.
1) p is even
(PROOF: 2 divides 1 6 − p 2 , and 1 6 so 2 divides also p 2 and (since 2 is prime) p must be even.)
2) p is NOT a multiply of 3
(PROOF: otherwise 3 would divide 1 6 − p 2 and p 2 and that should imply that 3 divides 1 6 )
3) 4 < p < 1 1
(PROOF: because the two members of the equation must be either both negative or both positive (or both zero of course) ).
These 3 facts imply that p ∈ { 8 , 1 0 } .
We can try these two values on the equation and from
n = 2 ( p − 1 2 ) 1 6 − p 2
we get two possible values for n namely
n = 6 , n = 2 1
For n = 6 we get the initial expression to be the square of n + p = 8 + 6 = 1 4 .
For n = 2 1 we get the initial expression to be the square of n + p = 2 1 + 1 0 = 3 1 .
So the largest n requested is 2 1 .
Complete the square to get (n+12)^2-128=A^2
Where A is an integer.
Let S=n+12
S^2-128=A^2 (Equation 1)
Inspecting the sequence of square numbers 1,4,9.16,25......... We can see the differences are 3,5,7,9...... i.e. the increases increase by 2 each time.
We can write that for any square K^2 it has increased from the previous square number by 2K-1 (call this equation 2). e.g. 5^2=4^2+(2x5-1)
Therefore to maximise S (and hence n) we must find square numbers that have a difference of 128 (by looking at equation 1) and preferrably make them as close as possible to maximise.
Clearly all the diffferences between the squares are odd 3,5,7,9....... So S and A cannot be consecutive as their difference is 128 if they are squared. Therefore introduce a number Z between them so the number line looks like:
1,2,3.............A,Z,S.............
Let the difference between A^2 and Z^2 be denoted as D. Hence the difference between Z^2 and S^2 is D+2. As D and D+2 must add to 128, D=63 (2D+2=128).
A^2+63=Z^2
Using Equation 2 2Z-1=63 Z=32 Hence S=33 And therefore n=21 as S=n+12.
Let n 2 + 2 4 n + 1 6 = m 2
Since n ∈ I so D = k 2 where k ∈ I , D is the discriminant of the equation
D = b 2 − 4 a c = 5 1 2 + 4 m 2 = k 2
⇒ 5 1 2 = ( k − 2 m ) ( k + 2 m )
Largest value of m = 3 1
Substitute the value m in the starting equation yo get
n 2 + 2 4 n − 9 4 5 = 0
( n − 2 1 ) ( n + 4 5 ) = 0
n m a x = 2 1
This solution is marked incomplete. Priyanshu Mishra brought up a valid point, how did you get the largest value of m as 3 1 ?
Nice solution. but can i am unable to understand that how you can say that largest possible m is 31. Explain me clearly.
Problem Loading...
Note Loading...
Set Loading...
write it as n 2 + 2 4 n + 1 6 = n 2 + 2 4 n + 1 4 4 − 1 2 8 = ( n + 1 2 ) 2 − 2 7 substitute n + 1 2 = z , and let the whole expresion be t 2 z 2 − 2 7 = t 2 ⟶ ( z − t ) ( z + t ) = 2 7 now, lets say z − t = y , z + t = x then 2 z = x + y to attain the max of z, y must be as big as possible ( z − t ) ( z + t ) = 2 × 2 6 ⟶ z − t = 2 , z + t = 6 4 2 z m a x = 6 6 ⟶ z m a x = 3 3 since z = n + 1 2 ( n + 1 2 ) m a x = 3 3 ⟶ n m a x = 2 1